The effect of output unit choice on detection of feedstock effects on chipper productivity and fuel consumption. (December 2018) - Eliasson, Lars; Fridh, Lars; Spinelli, Raffaele
Abstract: Currently different trade units are used throughout the forest energy supply chain in Sweden: chipping contractors are paid per m 3 chipped volume, dry metric tonnes or MWh, hauliers per raw tonnes or m 3 chipped volume and the company supplying the chips to the heating plant most often per delivered MWh. This introduces business risks for all market players, and affects studies of chipping equipment. Lately, Skogforsk has used oven dry tonnes, but stakeholders that measure chips in other units want results to be presented in these units as well. To raise awareness about output unit selection and its effect on productivity and fuel consumption studies, Bruks 806 chippers were studied when chipping spruce and beech residues. Results show that the selection of output unit affects the capacity of detecting treatment differences and the direction of such differences. Chipping productivity based on effective chipping time was higher for spruce residues when calculated using chipped volume, and for beech when calculated using raw weight. Similar trends were found for fuel consumption per product unit. As both feedstock characteristics and output measurement unit selection affects study results, a proper experimental design to control these effects is important. In many cases it is a matter of keeping feedstock constant during comparisons of machines/treatments. Care is needed when using chipped volume, as chipper settings may influence chip bulk density and thus chip volume. The use of different units throughout the supply chain reduces transparency and increases the risk for sub-optimal decisions. Highlights: Output unit affects the possibility to detect differences in chipper efficiency. The direction of treatment differences may depend on the choice of output unit. Output unit choice is an issue when comparing feedstocks or published results. Effects of output unit choice can be controlled by a proper experimental design.